Influence of juvenile idiopathic arthritis on the quality of life of young adults in the transition period to adult rheumatologic care - Marta Dzhus (Psihosomatična Medicina ta Zagalʹna Praktika, 2017)
Background. Young adults with juvenile idiopathic arthritis (JIA) often have an active disease with significant functional impairment in adulthood that can affect their physical and mental functions.